IMPLEMENTATION OF THE INFORMATION SYSTEM OF PRELIMINARY NOTIFICATION ABOUT PASSENGERS AT RAILWAY AND AIR CHECKPOINTS - Kantorov, Roman (Border Security and Management, 2016)
The aim of the study is to analyze the process of implementing and putting into practice the Information System of Preliminary Notification about Passengers at Railway and Air checkpoints into the activity of the Border Guard Service of the Republic of Belarus. The main tasks of the study are as follows: to analyze the practical methods of operating of the Information System during the border control’s procedures at railway and air checkpoints; to estimate the functional practice of the Information System at railway and air checkpoints of Belarus. The study under consideration is fundamentally based on the dialectical-philosophical method alongside with general scientific and specific scientific methods. Background of the System’s implementing, achieved results and directions for further development